Riemannian geometry and geometric analysis - Jost, Jurgen 1956- (Universitext, 2011)
This established reference work continues to lead its readers to some of the hottest topics of contemporary mathematical research. The previous edition already introduced and explained the ideas of the parabolic methods that had found a spectacular success in the work of Perelman at the examples of closed geodesics and harmonic forms. It also discussed further examples of geometric variational problems from quantum field theory, another source of profound new ideas and methods in geometry. The 6th edition includes a systematic treatment of eigenvalues of Riemannian manifolds and several other additions. Also, the entire material has been reorganized in order to improve the coherence of the book. From the reviews: This book provides a very readable introduction to Riemannian geometry and geometric analysis. With the vast development of the mathematical subject of geometric analysis, the present textbook is most welcome. Mathematical Reviews the material is self-contained. Each chapter ends with a set of exercises. Most of the paragraphs have a section 'Perspectives', written with the aim to place the material in a broader context and explain further results and directions. Zentralblatt MATH?